2006
DOI: 10.1897/05-415r.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of mixtures of antibiotics used in aquacultures

Abstract: More or less well-defined mixtures of antibiotics used in aquacultures may be distributed in the aquatic environment. Therefore, a systematic mixture ecotoxicity study was performed with the aquaculture antibiotics oxytetracycline, oxolinic acid, erythromycin, florfenicol, and flumequine. Test organisms were freshwater algae (Pseudokirchneriella subcapitata), activated sludge microorganisms, and luminescent bacteria (Vibrio fischeri). Design and statistical analysis of test results were based on isobolographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(76 citation statements)
references
References 27 publications
4
67
0
5
Order By: Relevance
“…Yet, in the classical acute Microtox test with V. fischeri as test organism, no effects were observed for any of the test compounds after 30 min of exposure. This is in agreement with previous studies applying the Microtox test (Ferrari et al, 2004;Isidori et al, 2005;Christensen et al, 2006) and is most likely due to the very short exposure time (15-30 min) rather than to insensitivity of V. fischeri to antibiotics. This is confirmed by Thomulka et al (1993) who reported substantial effects of several antibiotics on reproduction of the microbe Vibrio harveyi after 5 h of exposure, but obtained little evidence for shortterm effects on bioluminescence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yet, in the classical acute Microtox test with V. fischeri as test organism, no effects were observed for any of the test compounds after 30 min of exposure. This is in agreement with previous studies applying the Microtox test (Ferrari et al, 2004;Isidori et al, 2005;Christensen et al, 2006) and is most likely due to the very short exposure time (15-30 min) rather than to insensitivity of V. fischeri to antibiotics. This is confirmed by Thomulka et al (1993) who reported substantial effects of several antibiotics on reproduction of the microbe Vibrio harveyi after 5 h of exposure, but obtained little evidence for shortterm effects on bioluminescence.…”
Section: Discussionsupporting
confidence: 92%
“…04.011 expected that toxicity assessment with bacteria would provide a sensitive method to determine the effects of antibiotics in the aquatic environment. Yet, the classical acute Microtox test system, with a marine bacterium (Vibrio fischeri) as test organism, has not proven very sensitive to antibiotics (Ferrari et al, 2004;Isidori et al, 2005;Christensen et al, 2006). Alternatively, cyanobacteria could be used as test organisms and it has indeed been found that cyanobacteria were up to two orders more sensitive to antibiotics than green algae (Holten-Lützhøft et al, 1999;Halling-Sørensen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Slight deviations ( predicted EC 50 values lower than predicted by a factor of roughly 2-unfortunately, the authors do not provide numerical values for the observed and predicted EC 50 s) from the predictions by CA and IA were also observed by Schnell et al [53] for an equitoxic mixture of diclofenac, bezafibrate, fluvoxamine, musk ketone and galaxolide. Clear synergistic effects to algae were observed for mixtures of flumequine þ erythromycin and oxytetracycline þ flumequine by Christensen [45].…”
Section: Deviations From Concentration Addition And/or Independent Acmentioning
confidence: 96%
“…These drugs are applied as a means to treat diseased fishes or for prevention of diseases (Christensen et al, 2006) as the production may get hampered by unpredictable mortalities that may be due to negative interactions between fish and pathogenic bacteria. Although they are used to improve aquaculture production, residues of these antibiotics and chemicals could influence quality of the final product.…”
Section: Introductionmentioning
confidence: 99%